INTEGRACIÓN DE LA EMPRESA A LA COMUNIDAD: UN CASO DE RESPONSABILIDAD SOCIAL EMPRESARIAL EN EL PERÚ - Quiroz Morales, Patricia (2009)
The corporate social responsibility activities launched by the Peruvian mining enterprises have had particular importance in recent years, especially those activities connected to the communities where these companies work. Some communities have assumed an active role in the decisions that are related with their economic and social development. This behavior is the result of an integrated approach of citizen empowerment and building capacities for sustainable development; companies, civil society, local governments and the community work together looking for a same goal. This paper shows the project of Health and Nutrition called “Ally Micuy” in Ancash, Peru was launched by “Compañía Minera Antamina S.A.”. This program focus to reduce 3% of chronic malnutrition in children of Region Ancash. The program empowered the local population in best practices of health and nutrition. The results of the program indicate that collective participation in the decision-making promotes the sustainable development of the community.